The many faces of Jesus Christ intercultural Christology - Küster, Volker 1962- (Maryknoll, NY Orbis Books, 2023)
"Updated version of an Orbis classic"--
Includes bibliographical references and index
Keywords: Jesus Christ -- Person and offices; Christianity and culture -- Developing countries